Paternal lineage of the Berbers from Aurès in Algeria: estimate of their genetic variation - Amine Abdeli; Traki Benhassine (Taylor & Francis Group, 2019)
Background: Aurès is a vast territory in the east of Algeria, characterised by its traditional Berber settlement which has preserved its language and its rich history; its name goes back to antiquity and before the Roman conquest it was part of the territory of ancient Numidia. The Chaoui people in this region are one of Algeria's largest Berber groups. Aim: The aims were to investigate the level of genetic diversity of the Berbers of Aurès through the analysis of the paternal gene pool and to estimate the percentage of genetic variation among different geographical regions and linguistic groups from Algeria. Subjects and methods: Twenty-three Y-STRs were genotyped in a sample of 218 unrelated males of the Berbers of Aurès. Algorithms were used to estimate the Y-chromosome haplogroups. Genetic distance, non-metric MDS and AMOVA were used to analyse the genetic relationships between sample groups. Results: The paternal lineage of this sample of the Aurès region did not exhibit strong signals of differentiation with other samples from North-central, Northwest, and South Algeria. However, significant differences were found within this sample, demonstrating a high degree of heterogeneity. Conclusion: The results demonstrate that Aurès people are isolated and closed, but nevertheless have quite different genetic profiles.